The Impact of Corporate Social Responsibility (CSR) Programs on the Development of MSME Empowerment in the Manufacturing Sector - Afiffah Nur Arifin; Nurul Istiqomah; Sarjiyanto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Corporate Social Responsibility (CSR) has become a strategic instrument for manufacturing firms to address environmental and social challenges while simultaneously supporting the development of Micro, Small, and Medium Enterprises (MSMEs). This study aims to examine the impact of CSR programs on the development and empowerment of MSMEs in the manufacturing sector. A Systematic Literature Review (SLR) approach was employed to synthesize and analyze prior empirical studies published in Scopus-indexed journals between 2019 and 2023. The review process followed a structured protocol, including article identification, screening, eligibility assessment, and qualitative synthesis, resulting in nine highly relevant studies. The findings indicate that CSR implementation in the manufacturing sector positively contributes to MSME empowerment through improved access to resources, enhanced managerial and technical capabilities, increased market opportunities, and strengthened environmental awareness. CSR initiatives focusing on environmental management, energy efficiency, waste reduction, education, and community development were found to play a crucial role in mitigating the negative environmental impacts of manufacturing activities while fostering sustainable MSME growth. Furthermore, institutional pressures—normative, coercive, and mimetic—were identified as significant drivers influencing corporate engagement in CSR practices. Overall, this study highlights that CSR serves not only as a mechanism for corporate accountability but also as a catalyst for inclusive economic development and sustainability. The findings provide valuable insights for policymakers, practitioners, and manufacturing firms in designing effective CSR strategies that support MSME empowerment and promote long-term social, economic, and environmental sustainability.